Yield of plantain grown under different tree densities and slash and mulch versus slash and burn management in an agrisilvicultural system in southern Cameroon - Norgrove, L.; Hauser, S. (Elsevier, 2002)
Deforestation in the humid tropics poses an increasing threat to natural forests and future timber supplies. Smallholder slash and burn farming and timber extraction are the major causes of deforestation in the Congo basin. Therefore, the feasibility of an alternative to slash and burn, the combination of timber tree production (silviculture) with that of shade-tolerant plantains was tested. French plantain cv. ‘Essong’ (Musa sp. AAB) was grown as an understorey crop, with various crop management treatments: burning; mulching; and intercropping with tannia (Xanthosoma sagittifolium (L.) Schott) under two imposed timber stand densities (TSDs), replicated in four blocks, in a 6-year-old Terminalia ivorensis (A) Chev. timber plantation in southern Cameroon. No fertiliser, dressing, pesticide or herbicide was applied. Cumulative plant-crop (PC) yields at 1000 days after planting were higher in the low TSD than in the high TSD. The best treatment, low TSD, intercropped and mulched, produced 11.7 Mg ha−1 in the plant-crop. Losses were predominantly uprooting of plants.